2011
DOI: 10.1177/0888406411406553
|View full text |Cite
|
Sign up to set email alerts
|

Training Teachers to Use Pivotal Response Training With Children With Autism

Abstract: Although evidence-based practices (EBPs) for educating children with autism, such as pivotal response training (PRT), exist, teachers often lack adequate training to use these practices. The current investigation examined the efficacy of a 6-hour group workshop plus individual coaching for training 20 teachers to use PRT. Results indicate that the workshop alone was only effective in training 15% of the teachers to meet mastery criteria for PRT. The majority of teachers, however, showed additional improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 24 publications
1
54
1
7
Order By: Relevance
“…The results of this systematic review further demonstrated a large variability in the PRT techniques that were implemented across studies and revealed that only two studies incorporated all PRT techniques (i.e., Minjarez et al 2011;Suhrheinrich 2011). In particular, "gaining the child's attention and using contingent reinforcement" were often not incorporated or not specifically reported.…”
Section: Children With Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this systematic review further demonstrated a large variability in the PRT techniques that were implemented across studies and revealed that only two studies incorporated all PRT techniques (i.e., Minjarez et al 2011;Suhrheinrich 2011). In particular, "gaining the child's attention and using contingent reinforcement" were often not incorporated or not specifically reported.…”
Section: Children With Asdmentioning
confidence: 99%
“…In 29 studies, reinforcement of attempts at target behaviors was used. Two studies incorporated all seven PRT techniques (Minjarez et al 2011;Suhrheinrich 2011). Several studies incorporated additional intervention strategies, such as multiple cues (e.g., Pierce and Schreibman 1997b), modeling of target response (Stahmer 1995), prompting (e.g., Koegel et al 2012), prompt fading (e.g., Koegel et al 2010a), time delay (Koegel et al 1998a), and narrative play (e.g., Harper et al 2008).…”
Section: Intervention Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Special education licensure requirements are also not consistent from state to state leading to varying levels of knowledge for teacher candidates in the area related to meeting the needs of students with autism. This leaves educators unprepared to successfully meet the needs of students with ASD (Suhrheinrich, 2011). This lack of preparation also places teachers at a disadvantage because all teachers, in special and general education, will most likely have a student with ASD in their classroom and they need to be well versed in strategies to meet their unique needs (Loiacono & Valenti, 2010).…”
Section: Preservice Teacher Trainingmentioning
confidence: 99%
“…Stahmer (2007) showed that more than 70% to 80% of the teachers in the southern province of California are using PRT programs. Since PRT has been developed for the use in the natural environment, the classroom is an appropriate context for the application of PRT (Suhrheinrich, 2011).…”
Section: Natural Communication Interventionsmentioning
confidence: 99%